Development of coating material from epoxidized unripe fresh fruit bunch palm oil: article - Joibi, Aleeza April; Yaakob, Najmiddin (2020)
Unripe fresh fruit bunches (FFB) are typically rejected as it results in inferior quality palm oil, thus leading to wastage and losses. Repurposing the bunches to be used as a replacement for diglycidyl ether of bisphenol A (DGEBA) in a new epoxy coating formulation can increase the sustainability of paint industries. This also reduces the dependency on DGEBA as the conventional epoxy resin which has shown to cause adverse effects on human health based on past researches. Unripe fresh fruit bunch palm oil undergoes epoxidation process which adds an oxirane ring to the fatty acid (FA) structure. The oxirane ring provides a reactive site for the crosslinking reaction during the coating formulation. The formulated coating was tested for its chemical resistance through chemical immersion and solvent rub tests to determine the best coating formulation that can withstand various environments with minimal thickness loss. Fourier Transform Infrared (FTIR) Spectroscopy analysis showed the presence of oxirane ring after the epoxidation process. Results from the chemical immersion test and solvent rub test showed that the developed coating material experienced little to no corrosion and also minimal thickness loss when exposed to organic solvents such as acetone and toluene.